Growth, reproductive, and productive performance of Begait cattle under different herd management systems in northern Ethiopia - Mezgebe, Gebretnsae; Gizaw, Solomon; Urge, Mengistu (Springer, 2018)
The performance of indigenous Begait cattle (498 cows, 284 calves, and 48 heifers) in northern Ethiopia was studied. System of herd management significantly (P < 0.01) influenced all production traits. Calves in medium-input herds (MIHM) grew faster than those in low-input herds (LIHM), by 232 g/d from birth to 9 months (Gain1) and by 385 g/d from 9 to 12 months (Gain2). Cow’s dry period, calving interval (CI), and age at first calving (AFC) were 234, 222, and 343 days shorter for MIHM than for LIHM. Compared with LIHM, cows from MIHM had 74% higher daily milk yield (DMY) and 91% higher lactation milk yield (LMY). Calves born at wet season grew faster by 14 and 10% than those calves born in the dry season at Gain1 and Gain2. The subsequent CI of cows calved in the wet season had 77 days shorter, 0.45 kg DMY, and 93 kg LMY increment. The differences between production systems can be attributed to differences in management skills and access to better quality feeds. Technical intervention is needed to ensure provision of balanced rations to exploit the potential productivity of Begait cattle.